Computational modeling and bioinformatic analyses of functional mutations in drug target genes in Mycobacterium tuberculosis - Singh, Pooja; Jamal, Salma; Ahmed, Faraz; Saqib, Najumu; Mehra, Seema; Ali, Waseem; Roy, Deodutta; Ehtesham, Nasreen Z.; Hasnain, Seyed E. (Computational and structural biotechnology journal, 2021)
[Display omitted] •MycoTRAP-DB, a database of mutations and their impact on normal functionality of protein in M.tb genes.•Several secondary mutations were identified with significant impact on protein structure and function.•Comprehensive information gives insight for screening of suspected hotspots in advance to combat drug resistant TB. Tuberculosis (TB) continues to be the leading cause of deaths due to its persistent drug resistance and the consequent ineffectiveness of anti-TB treatment. Recent years witnessed huge amount of sequencing data, revealing mutations responsible for drug resistance. However, the lack of an up-to-date repository remains a barrier towards utilization of these data and identifying major mutations-associated with resistance. Amongst all mutations, non-synonymous mutations alter the amino acid sequence of a protein and have a much greater effect on pathogenicity. Hence, this type of gene mutation is of prime interest of the present study. The purpose of this study is to develop an updated database comprising almost all reported substitutions within the Mycobacterium tuberculosis (M.tb) drug target genes rpoB, inhA, katG, pncA, gyrA and gyrB. Various bioinformatics prediction tools were used to assess the structural and biophysical impacts of the resistance causing non-synonymous single nucleotide polymorphisms (nsSNPs) at the molecular level. This was followed by evaluating the impact of these mutations on binding affinity of the drugs to target proteins. We have developed a comprehensive online resource named MycoTRAP-DB (Mycobacterium tuberculosis Resistance Associated Polymorphisms Database) that connects mutations in genes with their structural, functional and pathogenic implications on protein. This database is accessible at http://139.59.12.92. This integrated platform would enable comprehensive analysis and prioritization of SNPs for the development of improved diagnostics and antimycobacterial medications. Moreover, our study puts forward secondary mutations that can be important for prognostic assessments of drug-resistance mechanism and actionable anti-TB drugs.